Bio-Inspired Nanodelivery Platform: Platelet Membrane-Cloaked Genistein Nanosystem for Targeted Lung Cancer Therapy - Gao R; Lin P; Yang W; Fang Z; Gao C; Cheng B; Fang J; Yu W (International Journal of Nanomedicine)
Rui Gao,1,* Peihong Lin,1,* Wenjing Yang,1,* Zhengyu Fang,1 Chunxiao Gao,1 Bin Cheng,2 Jie Fang,3 Wenying Yu1 1School of Pharmacy, Hangzhou Medical College, Hangzhou, 310013, People’s Republic of China; 2Department of Traditional Chinese Medicine, Zhejiang Pharmaceutical University, Ningbo, 315500, People’s Republic of China; 3Zhejiang Provincial Laboratory of Experimental Animal’s & Nonclinical Laboratory Studies, Hangzhou Medical College, Hangzhou, 310013, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bin Cheng; Wenying Yu, Email 44418972@qq.com; zjyuwenying@163.comBackground: Genistein (Gen), a natural polyphenolic compound, has emerged as a promising candidate for lung cancer treatment. However, the potential clinical application of Gen is limited due to its poor solubility, low bioavailability, and toxic side effects. To address these challenges, a biomimetic delivery platform with cell membranes derived from natural cells as carrier material was constructed. This innovative approach aims to facilitate targeted drug delivery and solve the problem of biocompatibility of synthetic materials.Methods: First, the liposomes (LPs) loaded with Gen (LPs@Gen) was prepared using the ethanol injection method. Subsequently, PLTM-LPs@Gen was obtained through co-extrusion after mixing platelet membrane (PLTM) and LPs@Gen. Additionally, the biological and physicochemical properties of PLTM-LPs@Gen were investigated. Finally, the targeting ability, therapeutic efficacy, and safety of PLTM-LPs@Gen for lung cancer were evaluated using both a cell model and a tumor-bearing nude mouse model.Results: The optimal preparation ratio for LPs@Gen was Gen: soybean lecithin: cholesterol: DSPE-PEG2000 (3:30:5:10, mass ratio), while the ideal fusion ratio of LPs@Gen and PLTM was 1:1. The particle size of PLTM-LPs@Gen was 108.33 ± 1.06 nm, and the encapsulation efficiency and drug loading were 94.29% and 3.09% respectively. Gen was released continuously and slowly from PLTM-LPs@Gen. Moreover, PLTM-LPs@Gen exhibited good stability within one week. The results of in vitro cellular uptake and in vivo distribution experiments indicated that the carrier material, PLTM-LPs, has the immune escape ability and tumor targeting ability. Consequently, it showed better therapeutic effects than free drugs and traditional LPs in vitro and in vivo tumor models. In addition, safety experiments demonstrated that PLTM-LPs@Gen possesses good biocompatibility.Conclusion: Biomimetic nanomedicine provides a new strategy for the precision treatment of lung cancer in clinical practice.Keywords: bionic technology, platelet membrane, genistein, liposomes, lung cancer, targeted therapy